Electronic Properties of Sn- or Ge-Doped In2O3 Semiconductors - S. J. Wen; G. Campet (Active and Passive Electronic Components)
The thermoelectric power and Hall effect of In2O3 single crystals, either undoped or Sn doped, and of In2O3 ceramics, either undoped or Sn or Ge doped, are investigated. All doped samples have negative thermoelectric power values. The metal-type conductivity occurs when the carrier concentration exceeds l019 cm–3 The correspondence between the values of the thermoelectric power and those of the carrier mobility and carrier concentration is given. Most interestingly this study puts into light the enhanced carrier mobility occurring for Ge-doped In2O3 samples compared with ITO samples (Sn-doped In2O3 widely used in optoelectronic devices.